2021
DOI: 10.1016/j.ijcard.2020.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in activation of remote monitoring in patients with cardiac rhythm devices during the coronavirus (COVID-19) pandemic

Abstract: Background Remote monitoring (RM) technology embedded in cardiac rhythm devices permits continuous monitoring of device function, and recording of selected cardiac physiological parameters and cardiac arrhythmias and may be of utmost utility during Coronavirus (COVID-19) pandemic, when in-person office visit for regular follow-up were postponed. However, patients not alredy followed-up via RM represent a challenging group of patients to be managed during the lockdown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…As also reported in several studies, not only does RM play a central role in preventing hospitalizations and improving survival and quality of life in patients with CIEDs, it is also a cost‐effective alternative to in‐person evaluations 16–25 . Overall, in the context of the COVID‐19 emergency, the improvement of RM coverage has facilitated continuous patient assistance and significantly reduced the risk of virus transmission among both more vulnerable populations and healthcare providers 26–28 …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…As also reported in several studies, not only does RM play a central role in preventing hospitalizations and improving survival and quality of life in patients with CIEDs, it is also a cost‐effective alternative to in‐person evaluations 16–25 . Overall, in the context of the COVID‐19 emergency, the improvement of RM coverage has facilitated continuous patient assistance and significantly reduced the risk of virus transmission among both more vulnerable populations and healthcare providers 26–28 …”
Section: Discussionmentioning
confidence: 80%
“…[16][17][18][19][20][21][22][23][24][25] Overall, in the context of the COVID-19 emergency, the improvement of RM coverage has facilitated continuous patient assistance and significantly reduced the risk of virus transmission among both more vulnerable populations and healthcare providers. [26][27][28] Our Italian multicenter study involved patients from different cen- were monitoring at least 50 patients via this system. The increased number of patients enrolled was achieved thanks to the competence of the staff and their ability to reinforce patients' feeling of being constantly assisted, both technically and clinically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way the medical service responds to alerts also has a great impact on outcomes; however, this requires adequate organization and resources in these centers to promote effective and immediate follow up. 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Expert recommendations emphasized the potential benefits of remote monitoring in non-CIED heart failure patient group for potential better and safer patient management during COVID-19 pandemic related healthcare restrictions [8,9] and expert position statements were published for reducing in-office patient evaluation follow-up burden and face-to-face visit events resulting in potential minimised exposure of patients and healthcare workers [8,[10][11][12]. Some authors suggested consequent activation of RM function in all newly implated CIEDs [13], or declared RM as essential in the follow-up of CIED patients during the pandemic [14,15]. Aim of this study was to investigate, wheter symptomatic heart failure patients, with implanted defibrillators (ICD) or cardiac resynchronization therapy pacemakers (CRT-P) or defibrillators (CRT-D) capable to remote follow-up may have clinical benefits in terms of rapid detection of worsening heart failure or other clinival adverse events compared to a conventionally followed (non-monitored) patient group during the special scenario of COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%